The roles of small‐scale topographic perturbations in precipitation forecasting using a convection‐permitting ensemble prediction system over southern China. (6th July 2022) - Wang, Jingzhuo; Chen, Jing; Xue, Haile; Li, Hongqi; Zhang, Hanbin
Abstract: The effects of small‐scale topographic perturbations on precipitation forecasts are investigated using the China Meteorological Administration's Convection‐Permitting Ensemble Prediction System. Southern China is chosen as the study domain because complex terrain is located there and heavy rainfall frequently occurs. The investigation comprises seven cases including strong and weak forcings on the synoptic scale in terms of convective adjustment time‐scale and synoptic conditions. To construct the topographic perturbation scheme, the standard deviations of small‐scale topographic heights and random fields were first introduced, and sensitivity runs with different topographic perturbation magnitudes were performed at a 3‐km horizontal grid spacing. The results indicate that the model runs with a single topographic perturbation show small changes in precipitation forecasts on strong‐forcing cases and more important impacts for weak‐forcing events, but the effect is also restricted to the control forecast skills. In addition, the topographic perturbation impacts the precipitation forecasts through dynamic processes, and the impact areas are mainly found at locations with rainstorms and heavy rainstorms in the observations. Moreover, the precipitation forecasts react sensitively to the topographic perturbation magnitude, with a larger topographic perturbation magnitude leading to larger amplitudes and spatial gain of precipitation ensemble spread, as well as a better Brier score. However, the selection of the perturbation magnitude is also influenced by the standard deviations of the small‐scale topographic heights. Abstract : The topography plays an important role in the formation, development and distribution of extraordinary rainfall, and convection‐permitting models are considered a useful tool to research the effects of topography on precipitation forecasts. However, the topography exists the uncertainties owing to the deficiencies of handling the topography in the numerical model. Therefore, this study constructed a small‐scale topographic perturbation scheme and then investigated the influence of topographic perturbation on precipitation forecasts using a convection‐permitting ensemble prediction system over southern China.